Effect of transcranial direct current stimulation on swallowing improvement and cortical activity in hemispheric stroke patients: a randomized, controlled trial - Guoping Duan; Ying Yuan; Heliu Hua; Xu Zhang; Baohu Liu; Yuanyuan Li; Jiayi Zhao; Qiuyue Wang; Jie Wang; Dongyu Wu (Scientific Reports)
Abstract Transcranial direct current stimulation (tDCS) has been extensively utilized in the treatment of post-stroke dysphagia; however, the effect of different tDCS protocols remains uncertain. This study aims to investigate the effect of tDCS on dysphagia after hemispheric stroke and compare the effect of tDCS among three protocols. A total of 90 hemispheric stroke patients were randomized into three groups: bilateral, contralesional, and ipsilesional tDCS. Each group received anodal tDCS over the orofacial sensorimotor cortex (S1M1) of the bilateral, contralesional, and ipsilesional hemispheres, respectively, administered for 20 sessions overall, combined with exercise-based swallowing therapy. After tDCS, both the dysphagia assessment scale and the swallow severity scale showed significant improvement in all three groups (all p < 0.01). In the comparisons among the three groups, the bilateral tDCS demonstrated significantly greater improvement than the contralesional and ipsilesional tDCS group in terms of the dysphagia assessment scale (all p < 0.001), and superior to contralesional tDCS group in terms of the swallow severity scale (p = 0.019). The analysis of ApEn showed increased cortical activity in both stimulated and non-stimulated areas of bilateral hemispheres after bilateral and unilateral tDCS. Moreover, larger cortical areas of bilateral hemispheres were activated after bilateral tDCS, compared to those after unilateral tDCS. Trial registration Chinese Clinical Trial Registry Identifier: ChiCTR-TRC-14004955, 16/07/2014.